Parental Support, Academic Emotion, Learning Strategy, and Academic Achievement on First Year Student - Rizky Amalia; Melly Latifah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
The new challenges for first-year students potentially to influence their academic achievement. This study aimed to analyze the characteristics of students and families, parental support, academic emotions, and learning strategies and their effects on the academic achievement of first-year students. Determination of research location by purposive at Institut Pertanian Bogor. An example of this study is a total of 110 students of the Program Pendidikan Kompetensi Umum (PPKU) selected by simple random sampling. The results found that parental support related to emotional and instrumental aspects, positive and negative academic emotions were significantly correlated with the use of learning strategies. The dimension of learning strategy that is time and environment management and effort learning correlated on academic achievement.